Diaphragmatic Hernia following Pediatric Liver Transplantation: An Underappreciated Complication Prone to Recur - Waldron, Lea Sibylle; Cerisuelo, Miriam Cortes; Lo, Denise; Sayed, Blayne Amir; Vilca-Melendez, Hector; Magliocca, Joseph; Lurz, Eberhard; Baumann, Ulrich; Vondran, Florian W. R.; Richter, Nicolas; von Schweinitz, Dietrich; Guba, Markus; Muensterer, Oliver J.; Berger, Michael (European Journal of Pediatric Surgery, 2020)
Introduction Postoperative diaphragmatic hernia (DH) is a rare but potentially life-threatening complication following pediatric liver transplantation (LT). In the current literature, a total of 49 such hernias have been reported in 17 case series. We present eight additional cases, three of which reoccurred after surgical correction, and review the current literature with a focus on recurrence.Materials and Methods The study sample included children (<18 years of age) who underwent LT between June 2013 and June 2020 at five large transplant centers and who subsequently presented with DH. During the study period, a total of 907 LT was performed. Eight DH were recognized, and risk factors were analyzed.Results For the eight children with DH, the mean age at LT was 28.0 (5–132) months. All patients with a DH received left lateral segment split grafts except one, who received a full left lobe. The mean weight at time of LT was 11.8 (6.6–34) kg. Two patients had a primary abdominal muscle closure, and six had a temporary silastic mesh closure. All eight children presented with a right posterolateral DH. The small bowel was herniated in the majority of cases. Symptoms reported included nausea, vomiting, and respiratory distress. Two patients were asymptomatic, and discovery was incidental. All patients underwent prompt primary surgical repair. Three DH hernias (37.5%) recurred despite successful surgical correction.Conclusion DH following liver transplant with technical variant grafts may be underreported and is prone to recur despite surgical correction. A better understanding of the pathophysiology and more thorough reporting may help increase awareness. Early detection and prompt surgical management are the cornerstones of a successful outcome.
Keywords: pediatric liver transplantation; diaphragmatic hernia; liver surgery